Exposure to interparental violence and justification of intimate partner violence among women in Papua New Guinea - Richard Gyan Aboagye; Bernard Yeboah-Asiamah Asare; Collins Adu; Abdul Cadri; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Sanni Yaya (BMC Women's Health, 2023)
Abstract Background Previous studies have demonstrated that exposure to interparental violence is associated with intimate partner violence justification in a variety of contexts. In this study, we examined the association between exposure to interparental violence and justification of intimate partner violence among women in Papua New Guinea. Methods We used data from the 2016–18 Papua New Guinea Demographic and Health Survey. We included 2839 women of reproductive age (15–49 years) in a sexual union (married and cohabiting) in the study. We used a multivariable binary multilevel regression analysis to examine the association between interparental violence and justification of intimate partner violence. We presented the results of the regression analysis using crude odds ratio (cOR) and adjusted odds ratios (aORs), with their 95% confidence intervals (CIs). Results Women exposed to interparental violence were 1.26 (95%CI = 1.05, 1.53) times more likely to justify intimate partner violence than those who were not exposed. Women who resided in the Highlands (aOR = 2.50, 95%CI = 1.78, 3.51), Momase (aOR = 1.96, 95%CI = 1.40, 2.75), and Islands (aOR = 1.42, 95%CI = 1.01, 1.99) were more likely to justify intimate partner violence compared to those in the Southern region. Women who were exposed to one (aOR = 1.38, 95%CI = 1.06, 1.82) mass media were more likely to justify intimate partner violence compared to those who had no exposure to mass media. On the other hand, women aged 25–34 years (aOR = 0.66, 95%CI = 0.48, 0.91) and 35–49 years (aOR = 0.66, 95%CI = 0.44, 0.97) were less likely to justify intimate partner violence compared to those aged 15–24 years. Conclusions Our study has shown that exposure to interparental violence is a predictor of intimate partner violence justification. This study suggests the need for conscious and continuous efforts to identify and assist women who have been exposed to interparental violence to help prevent its transition to later life. Policies and interventions should be developed and implemented to curtail children’s exposure to domestic violence in their households. Also, laws and policies need to condemn any violence and demystify community justification and acceptance of intimate partner violence, taking into consideration the significant sociodemographic characteristics of the women highlighted in the study.